Genetic Erosion in Captive Alpine Musk Deer Highlights the Challenges of Conserving Endangered Species in Closed Populations - Han Jiang; Luyao Hai; Zhengwei Luo; Xianna Lan; Mi Zhou; Xinghu Qin; Defu Hu (Animals)
The alpine musk deer (Moschus chrysogaster) is a critically endangered species in China whose wild populations have precipitously declined due to habitat degradation and poaching. In response, China established the world’s first captive breeding facility for this species in 1990. Despite over three decades of closed breeding, the genetic consequences of long-term captivity remain unclear. Here, we present the first comprehensive assessment of mitochondrial genetic diversity in a captive population of 409 individuals, using three mitochondrial markers (D-loop, Cytb, and COI) and comparative data from wild conspecifics. Our results reveal a pronounced reduction in genetic diversity in the captive population compared to wild populations. Nucleotide diversity (π) and haplotype diversity (Hd) were consistently lower across all markers in captivity, with D-loop Hd = 0.639 and π = 0.01073. Further combined sequence analysis revealed a single dominant haplotype (Hap4) representing 56.99% of individuals, indicative of severe haplotype loss and homogenization. Although some haplotypes are shared with wild populations, captive populations exhibit strong genetic differentiation from wild populations, with the captive populations retaining only a limited fraction of the species’ maternal lineages. This pronounced genetic erosion driven by strong founder effects and genetic drift raises concerns about the viability and reintroduction success of this species. These findings highlight the inherent limitations of closed captive populations in preserving evolutionary potential and adaptive capacity. Our study emphasizes the urgent need for evidence-based genetic management, including founder augmentation and population exchange, to mitigate inbreeding and maintain genetic diversity.